UNDERSTANDING THE ESSENCE OF OMNICHANNEL IN INDONESIA'S EMERGING DIGITAL MARKETING ERA FOR BETTER CUSTOMER EXPERIENCE - Alam Shafira, Aura
As global economies and societies continuously evolve with technological advancements and environmental influences, the concept of sustainability is undergoing a significant change. Unexpected challenges, particularly the COVID-19 pandemic, have caused major transformations, affecting how companies operate and adapt to meet emerging needs. This paper explores into the paradigm shift occurring within the field of sustainability in Indonesia, especially focusing on how the pandemic has expedited a widespread transition to digital operations in businesses. With limited human interaction and strict health protocols, businesses have been compelled to migrate online to maintain continuity. While the shift to e-commerce has been effective in some respects, it has also underscored new vulnerabilities and brought attention to an often-overlooked aspect—customer loyalty. In the race for survival, many businesses focused on scaling their online presence to compensate for physical limitations. However, in the rush to expand digitally, they often neglected to foster deeper connections with their customers. By prioritizing growth over engagement, companies inadvertently created a gap in brand loyalty, leaving consumers disconnected and, in some cases, dissatisfied. This paper argues that businesses need to innovate and implement sustainable practices that keep customer engagement at the core to build long-term brand loyalty. Failure to adapt in this way will expose businesses to increased competition and could potentially erode their customer base. Through this research, I aim to identify the root causes behind the adoption of omnichannel marketing in Indonesian businesses and to analyse consumer responses to this approach. This research employs a mixed-methods methodology, blending qualitative and quantitative approaches. Primary research consists of an in-depth literature review, examining 30 relevant literature that provide a comprehensive understanding of omnichannel marketing and its implications. Secondary research involves surveys conducted with Indonesian consumers to gain insight into their experiences and perceptions regarding digital transformations in retail. The literature review reveals a significant shift towards e-commerce among Indonesian businesses, largely driven by the necessity to engage customers online during the pandemic. Yet, survey data collected shows that while consumers appreciated the convenience of e-commerce during this period, they have increasing concerns about security vulnerabilities, such as the rising incidence of cyberattacks on online platforms. These risks not only threaten customer trust but also pose long-term sustainability challenges for companies. Many consumers are also relatively unaware of the sustainability issues associated with digital business models, while others have directly experienced negative consequences, such as compromised personal data, adding pressure on businesses to adopt more secure and reliable digital practices. The study's findings indicate that sustainability will remain a challenge for businesses and consumers alike. Companies are now confronted with the dual responsibility of meeting evolving consumer expectations while establishing great security measures that protect customer data. Balancing these priorities is crucial for long-term viability, as customer trust in a brand's digital integrity directly influences loyalty and engagement. Companies must, therefore, focus on a holistic omnichannel approach that integrates consumer needs, prioritizes cybersecurity, and upholds sustainability commitments. In analysing why some Indonesian businesses have struggled to maintain a sustainable business model, this research also investigates how omnichannel principles, when implemented effectively, can enhance brand sustainability. By integrating digital marketing strategies and building a cohesive brand image across multiple platforms, businesses can create a more consistent and reliable experience for consumers, thereby strengthening loyalty. The study employs descriptive statistical methods to evaluate the collected data, shedding light on key areas where omnichannel approaches require refinement to ensure stable, long-term consumer relationships. Ultimately, this paper underscores the importance of redefining business strategies in alignment with digital and sustainable principles. For companies to thrive in today’s digital landscape, they must prioritize consumer engagement, address cybersecurity concerns, and foster a loyal customer base through meaningful omnichannel experiences. By doing so, businesses can not only compete more effectively but also contribute to a more resilient and sustainable economic future. The research findings support the hypothesis that omnichannel strategies need ongoing development and adjustment to maintain stability in a rapidly changing marketplace, with the ultimate goal of promoting a sustainable brand image that resonates with today’s discerning consumers.